مقصد الحرية عند ابن عاشور وتطبيقه في حقوق الإنسان - حليمي، محمد ضياء الحق; قوادر، عبدالباسط (جامعة أحمد دراية أدرار, 2024)
تهدف هذه الورقة البحثية والموسومة بـ: " مقصد الحرية عند ابن عاشور وتطبيقه في حقوق الإنسان" إلى بيان أهمية مقصد الحرية ومكانته في النسق المقاصدي للشريعة الإسلامية، وكيفية تفعيله في مختلف جوانب الحياة عموما وفي حقوق الإنسان على وجه الخصوص، معتمدين في ذلك على آراء محمد الطاهر ابن عاشور في هذا المجال، باعتباره من ابرز العلماء الذي قاموا بالتجديد في علم المقاصد في العصر الحديث، حيث اعتبره الكثير من الباحثين المجدد الثاني لعلم المقاصد بعد الشاطبي، لما تميز به من جرأة في تجديد وفهم الشريعة الإسلامية ومقاصدها، فكان من ثمار ذلك إن أضاف الكثير من المقاصد التي غفل عنها العلماء المتقدمين، والتي يعد مقصد الحرية من أهمها، كما لم يكتف بمجرد التقعيد والتنظير لها إنما انتقل بها إلى جانب التطبيق والتفعيل، من خلال تفعيل المقاصد عموما ومقصد الحرية خصوصا في مجالات الحياة المختلفة ومنها مجال حقوق الإنسان. This research paper, titled: “The purpose of freedom according to Ibn Ashour and its application to human rights”, aims to explain the importance of freedom and its place in the purposeful system of Islamic law, and how to activate it in various areas of life in general and in human rights in particular, relying in this on the opinions of Muhammad Al-Taher. Ibn Ashour in this field, as one of the most prominent scholars who renewed the science of objectives in the modern era, as many researchers considered him the second innovator of the science of objectives after Al-Shatibi, because of his boldness in renewing and understanding Islamic law and its objectives. One of the beneficial outcomes was that he added many purposes that were overlooked by earlier scholars, of which the purpose of freedom is one of the most important. He was not satisfied with merely restricting and theorizing about it, but rather moved it to the side of application and activation, by activating the purposes in general and the purpose of freedom in particular in the various areas of life, including the field of human rights.
Keywords: المقاصد الشرعية -- حق الحرية -- القيم الإسلامية -- ابن عاشور، محمد الطاهر، ت. 1393 هـ